2007
DOI: 10.1111/j.1468-3083.2006.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood acne, ephelides, warts, atopic dermatitis, psoriasis, alopecia areata and keloid in Kaohsiung County, Taiwan: a community‐based clinical survey

Abstract: Acne vulgaris is as common in Taiwan as in Western countries. Ephelides are not uncommon in our population with the main skin types III-IV. A clustered distribution of the wart infection was noted. The low prevalence of AD in Taiwan seems unaltered over the past decade. AA and psoriasis are rare in our series. Most keloids in our children are caused by BCG vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 37 publications
6
57
0
13
Order By: Relevance
“…The risk of warts was increased with taking part in work with an adjusted odds ratio of 1.5. Working during childhood is correlated with the socioeconomic status of the family, which in turn affects the incidence and prevalence of warts [19,24]. In our study, the prevalence of warts among children of families with lower income was 13.9%, as compared to only 7.8% in the higher income category.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The risk of warts was increased with taking part in work with an adjusted odds ratio of 1.5. Working during childhood is correlated with the socioeconomic status of the family, which in turn affects the incidence and prevalence of warts [19,24]. In our study, the prevalence of warts among children of families with lower income was 13.9%, as compared to only 7.8% in the higher income category.…”
Section: Discussionmentioning
confidence: 66%
“…Worldwide, there have been several studies on the prevalence of cutaneous warts among school children, showing a prevalence varying from 2.4% to 33% [6,7]. Several studies have revealed risk factors for the children and adolescents who contract warts that include low social class, practicing gymnastics and sports, taking part in work, a large family size, and keeping household animals [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hindistan'da okul çocuklarında (4-18 yaş) yapılan başka bir çalışmada ise akne prevalansı %8 olarak saptanmıştır 21 . Tayvan'da yapılan bir çalışmada 6-11 yaş arasındaki çocuklarda akne prevalansını ise %17,5 olarak bulunmuştur 22 . Ülkemizde ve diğer ülkelerde yapılan çalışmalardaki prevelans ile ilgili farklı değerler akne vulgarisin ırksal, genetik, sosyoekonomik ve çevresel faktörlerden etkilenmesiyle açıklanabilir.…”
Section: Discussionunclassified
“…Böylece prepubertal dönemde erkeklerde akne görülmezken, kızların küçük bir yüzdesinde pubertal döneme ait akne dışı bulgu yoktu. Bunun kızların pubertal gelişiminin erkeklere göre daha erken başlamasıyla ilişkili olduğu akla gelmektedir [19][20][21][22]28 . Pubertenin erken dönemlerindeki ve prepubertal dönemdeki akne, yerleşim yeri, akne lezyonlarının tipi ve tedavideki farklılıklarıyla adolesan dönemde görülen akneden bazı farklılıklar göstermektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation